Patterns of negotiation of meaning in English as second language learners interactions - Noordin, Nooreen; Abd. Samad, Arshad; Mukundan, Jayakaran; Samani, Ebrahim (Australian International Academic Centre, 2015)
Problem Statement: The Internet as a tool that presents many challenges has drawn the attention of researchers in the field of education and especially foreign language teaching. However, there has been a lack of information about the true nature of these environments. In recent years, determination of the patterns of negotiation of meaning as a way to delve in these environments has grown in popularity.